THE PROGRESS OF SUSTAINABLE DEVELOPMENT IN INDONESIA A COMPARISON OF SOCIAL ECONOMIC INDICATORS BETWEEN REGIONS - Roberto Akyuwen (Diponegoro University, 2011)
Global awareness and concept on the environmental friendly development has been emerged since early 1970s. However, the progress on its implementation was varied across countries. In Indonesia, sustainable development indicators have been studied and published by the Central Statistics Board (BPS) since 2002. Based on the recommendation of the United Na-tions Commission on Sustainable Development, those indicators were classified into two groups, i.e. environment indicators and social economic indicators. This paper is aimed to compare the progress of social economic indicators among provinces in Indonesia by using descriptive ap-proach. Observed indicators were including population, per capita gross domestic product (GDP), open unemployment, poverty, energy consumption, transportation, and agriculture. In addition, regional fiscal capacity and human development index among provinces were also analyzed. Although the fund transfer from central to local governments has increased signifi-cantly since the implementation of local autonomy and fiscal decentralization in 2001, however, in general, the improvement of social economic indicators were varied between provinces. Sev-eral provinces with high fiscal capacity were not able to improve its social economic indicators significantly. On the contrary, the other provinces with low fiscal capacity have achieved better social economic indicators. This phenomenon has proved the importance of having appropriate capability in managing local economic development.